Pengaruh Pemberian Sari Kacang Hijau Handmade terhadap Produksi Asi Ibu Menyusui di Kelurahan Selensen Wilayah Kerja Puskesmas Selensen Kabupaten Indragiri Hilir - Kurniati Kurniati; Fajar Sari Tanberika (Lembaga Pengembangan Kinerja Dosen, 2026)
Low breast milk production is a key barrier to successful exclusive breastfeeding. A non-pharmacological approach that may help is handmade mung bean (Vigna radiata) juice, which contains protein, vitamin B1, polyphenols, and flavonoids believed to stimulate prolactin secretion. This study examined the effect of handmade mung bean juice on breast milk production among breastfeeding mothers in Selensen Village, within the working area of Selensen Primary Health Center, Indragiri Hilir Regency. A quantitative Quasi-Experimental Post-Test Only Control Group Design was used. The population comprised 34 breastfeeding mothers, all included via total sampling and divided into an experimental group (n=17) and a control group (n=17). Data collection ran from 1–7 May 2026, using a breast milk production observation sheet. Univariate and bivariate analyses were performed with the Mann-Whitney test, following a Shapiro-Wilk test that indicated non-normal data distribution. Results showed that after intervention, 100% of the experimental group achieved smooth milk production, versus 64.7% in the control group. The Mann-Whitney test produced a p-value of 0.000 (p<0.05), confirming a significant effect. Handmade mung bean juice is recommended as a natural, accessible, low-cost complementary intervention midwife can promote to support exclusive breastfeeding